The Role of Product Quality and Price Perception in affecting Purchase Decision (Study on Milkmo Product) - Timotius F.C.W. Sutrisno; Gladys Greselda Gosal; Serin Fransisca Hernandes (Fakultas Bisnis, 2020)
This research aims to analyze the role of product quality and price perception in affecting purchase decision. The object of this study is Milkmo, which is a startup business that offers milk-based drink coated with chocolate syrup. This research distributes as many as 97 questionnaires to majority of male and female respondents aged 15 to 25 years old, using purposive sampling method. This research uses quantitative method by using multiple linear regression analysis. Based on the result of the research, it can be concluded that product quality and the perception of each price have significant effect on purchase decision of Milkmo product, therefore all hypotheses were upheld. This implies that the business owner should improve the quality of the product and set the price of the product carefully so they would not be rivaled by their competitors.